Secure Model of Access Control for Cloud Computing using Key Generation Based Public Cyclic Key Generation Method - Rahul Singhai, Ranjeet Osari (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Cloud computing is a big platform of service-oriented applications over the internet. The primary access control of cloud services using login credentials for users. The growing rate of malicious software breaks the security credentials of users and theft data, and blocks the services. To prevent security threats, cloud service providers and NIST design various access control using cryptography algorithms. However, the role-based access control mechanism has limitations and breaks the security bridge between users and service providers. This paper proposed key generation-based access control methods for accessing services and data over cloud computing. The proposed key generation approach is a public key generation algorithm, a cyclic key generation algorithm. The proposed key generation methods are implemented in the Java RMI model and MYSQL database. The proposed algorithm compares with RSA based key authentication approach. The experimental results suggest that the proposed algorithm is better than the existing algorithm of access control of cloud computing.